De betekenis van A. Kuypers gemene gratie - leer voor vandag - Douma, Jochem (Koers, 1986)
This article explores the meaning of Kuyper's doctrine of general grace for today, starting off with a consideration of grace and culture from the perspective of three possibilities: grace residing in opposition to, next to or within culture. Calvinism is posited as accepting the last view. The author explores Kuyper's harking back to predestination for a founding of general grace. This bestows meaning on everything, and the author subsequently explores this in more detail, looking at both main trends and by ways, and linking specific racial culture (according to Kuyper) very definitely with development. This leads to a consideration of Christendom and technology. This is followed by a critical evaluation of Kuyper’s doctrine, in the course of which it is delegated to a nine teenth century vision (in view of subsequent developments), more espe cially in view of the increasing secularization of the West, in contradistinction to Kuyper's earlier expectations of Calvinist expansion. This is also evident in Kuyper's views of the historical supremacy of the White races. It remains important, however, for the Calvinist to remain within culture, although in the final analysis the first priority should be the gospel of Christ and not the culture of people.